IN VITRO METHOD FOR EXPRESSION OF TOXIN PRODUCTION IN NON-TOXIGENIC CORYNEBACTERIUM SPP. WITH “SILENT” TOX-GENE - Gabrielyan, S. A. (Infekt͡s︡ii͡a︡ i immunitet, 2015)
The «in vitro method» for expression of toxin-production by phenotypically non-toxigenic strains of C. diphtheriae containing the “silent” toxin gene has been developed. The method can be characterised as rapid, economical, not demanding use of experimental animals, available to practical and scientific laboratories. Optimal conditions using this method were defined: nutrient mediums, frequency rate of passages, which provided restoration of toxin production. This method allowed to restore toxin-production in 10 out of 18 tested strains of C. diphtheriae with the “silent” toxin gene. Moreover, there was an increase of toxin roduction of by C. ulcerans and C. diphtheriae var. intermedius to the level allowing to detect toxin in the standard tests. The phenotype of a toxin-producing was defined by the Elek-test and ICS (immunechromatography set).